Swedish Historical Phenology Dataset - Langvall, Ola; Dahl, Åslög; Blomgren, Kjell (Swedish University of Agricultural Sciences, 2019)
The dataset contains reports of phenological observations, made at more than 700 locations throughout Sweden between 1865 and 1951. The observations were mainly conducted by local weather observers, assigned by the Swedish Weather Service (formerly named SMCA, now SMHI), so weather data can also be found for many of these locations, to support to the phenological observations. For weather data, contact SMHI (see www.smhi.se).

The dataset consists of 345 806 posts of phenology observations, in total. The main part of the phenological data consists of observations of budburst, flowering, ripening of fruits and autumn coloured leaves on plants and trees, but also spring and autumn migration of migratory birds, agricultural activities like when spring tillage begins and sowing and harvest begins, and also activities of a few insects.

The dataset was digitized and supplied by the Swedish National Phenology Network (SWE-NPN), a network lead by the Swedish University of Agricultural Sciences (SLU), and includes partners from several Swedish universities, governmental agencies and non-governmental organizations. Uppsala University and SMHI has contributed to this dataset, by digitizing the original forms, which they possess. For more information about the Phenology network, see www.swe-npn.se.

The phenological observations were made according to the protocol that was set by the SMCA (see uploaded files of the forms used by the observers, in Swedish). The observations was assessed regularly, on average once a week, or when needed, and the date when a new phenological phase occurred was noted in a form. Digital copies of the original forms are available on request. The dataset contains a file with observations, observation_standalone.csv, which can be used alone, without supporting files. This file contains all necessary information for using the data, e.g. coordinates (lat/long) for the location where the observation were made, species name (scientific), phenological phase and the date. The dataset also contains a file with observations, observation.csv, where the location, officiant, species and phenological phase are coded. To use this file, you need the supporting files included in the dataset, for locations, officiant names, species names and phenological phase descriptions.

Datasetet innehåller rapporter om fenologiska observationer gjorda på över 700 platser i Sverige mellan åren 1865 och 1951. Observationerna gjordes framför allt av SMCA:s (Sveriges Meteorologiska Centralanstalt, föregångaren till SMHI) lokala väderobservatörer och väderdata finns att tillgå för många ställen, som stöd till dessa observationer (kontakta SMHI för data-förfrågan, se www.smhi.se).

Datasetet omfattar totalt 345 806 poster med observationer. Fenologiska data består framför allt av observationer om lövsprickning, blomningstidpunkt, bärmognad och höstfärgning av löven hos växter och träd, men också ankomst- och flyttningsdatum för flyttfåglar, jordbruksaktiviteter som när vårbruket börjar och när sådd och skörd börjar, samt några insekters aktiviteter.

Datasetet är digitaliserat och tillhandahålls av Svenska fenologinätverket (SWE-NPN), ett nätverk med SLU som huvudman och flera universitet, myndigheter och intresseorganisationer som partners. Uppsala universitet och SMHI har varit samarbetspartners vid digitaliseringen, då de innehar originalblanketterna och har skannat in dessa till digitala kopior. För mer information om nätverket, se www.swe-npn.se.

De fenologiska observationerna gjordes enligt den instruktion som SMCA hade satt upp (se uppladdade originalblanketter i dokumentationen). Observationerna gjordes regelbundet, med ca 1 veckas mellanrum eller vid behov, och datum när en viss fas inträffat noterades på blankett. Digitala kopior av originalblanketterna kan erhållas på förfrågan. Datasetet innehåller en observationsfil, observation_standalone.csv, som kan användas helt separat, utan hjälpfiler. Denna innehåller all nödvändig information för att använda data, t.ex. koordinater (latitud/longitud) till lokalen där observationen är gjord, artnamn (latinskt), fenologisk fas samt tidpunkt. Det finns också en observationsfil, observation.csv, där plats, förrättare, art och fenologisk fas är kodade. Denna behöver övriga hjälpfiler som finns i datasetet, för att kunna kopplas till observationsplatser, förrättarens namn artnamn och fasbeskrivning.
Svenskt historiskt fenologidataset
Keywords: ecology; ekologi; seasonal variation; årstidsvariation; agriculture; jordbruk; climate change impact; klimatförändringarnas konsekvenser; phenology; Environmental monitoring facilities; Anläggningar för miljöövervakning; phenology; fenologi; Natural Sciences; Naturvetenskap; Climate Science; Klimatvetenskap; Environmental Sciences; Miljövetenskap; Physical Geography; Naturgeografi; Zoology; Zoologi; Ecology; Ekologi; Agricultural Science; Jordbruksvetenskap; Forest Science; Skogsvetenskap; Farming; Areella näringar; Biota; Biologi och ekologi